Stainless steel elastic intramedullary nailing of radius-ulna fractures in dogs - Meghwal, Kusum; Bishnoi, A.K.; Jyoti; Meena, Sonu; Bishnoi, Shivraj; Kumari, Anita; Lal, Mohan; Tanwar, Mahendra; Bishnoi, P. (Indian Journal of Veterinary Surgery, 2025)
Internal fixation of radius-ulna fractures was done in 9 dogs using stainless steel elastic intramedullary nail (EIN). The mean age and body weight of the animals were 26.44±6.93 months and 18.41±3.61 kg, respectively. Fracture fixation was done by open reduction by applying single nail in radius. In two cases, ulnar fracture was also fixed using EIN along with the radius. The mean percentage of medullary cavity occupied by the implant was 55.83±4.44% and the mean duration of surgery was 100.88±13.80 min. The median period of initiation of weight bearing on the operated limb was 4 days. In final outcome, limb function was excellent in 2 cases, very good in 5 cases, and good in 2 cases. Among 7 cases with intact nail, radiographic bone union was achieved in 6 cases and apparent callus with discernible fracture line in one case. Postoperative complications noted were exudative discharge from the suture line (n=3), suture dehiscence (n=2), carpal joint stiffness (n=3), backward migration of nail from inserted site (n=4), nail breakage at fracture site (n=1), carpus valgus (n=1), and osteomyelitis (n=3). From this study it was concluded that intramedullary fixation with elastic nail provided stable fixation of radial fractures in light weight dogs, but the technique was time consuming and care was needed to avoid complications during the fixation of nail.